Certain Investigation on Euler Matrix Method for Linear Second-Order Partial Differential Equations with Various Conditions: Application of Euler Matrix Method to Linear Second-Order Partial Differential Equations (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this essay we are studying the nature of a linear secondary differential equation system with different requirements for the Euler matrix. This is the intention study is to apply the Euler matrix method to linear second order partial differential equations under the most general conditions. Error analysis of the method is presented. By using the residual correction procedure, the absolute error may be estimated. The effectiveness of the method is illustrated in numerical examples. Numerical results are overlapped with the theoretical results. Some important results are also discussed.